Fast Flux Reaction Approach for the Preparation of Sn2TiO4: Tuning Particle Sizes and Photocatalytic Properties. Issue 5 (1st January 2019) - O'Donnell, Shaun; Hamilton, Adam; Maggard, Paul A.
Abstract : The Sn2 TiO4 phase is a small-bandgap (Eg ∼ 1.6 eV) semiconductor with suitable band energies to drive photocatalytic water-splitting. A new fast flux reaction can be used to prepare high purity Sn2 TiO4 in reaction times of down to 5 minutes. Shorter reaction times (5 and 15 min) lead to nanosized particles while longer reaction times (24 hours) yield micron-sized particles. The nanoparticles show an increased bandgap size owing to quantum size effects in the weak confinement regime (r >> aB ), increasing by ∼0.3 eV from 1.60 eV to 1.89 eV (indirect). From Mott-Schottky analyses, the conduction band edge is found to shift to slightly more negative potentials while the valence band edge exhibits a relatively larger positive shift. Calculations show this arises from the more disperse Sn s -orbital bands at the top of the valence band, compared the large Ti-based d -orbital band at the bottom of the conduction band. The photocatalytic activities of the Sn2 TiO4 nanoparticles for molecular hydrogen and oxygen production showed higher rates than the equivalent micron-sized particles as a result of both higher surface areas and higher overpotentials to drive each of the half reactions.